Stimulation of Growth and Alteration of Hormones by Elevated Carbon Dioxide for Creeping Bentgrass Exposed to Drought. Issue 4 (1st July 2019) - Burgess, P.; Chapman, C.; Zhang, X.; Huang, B.
ABSTRACT: Drought stress inhibits shoot growth of cool‐season turfgrass species, and elevated CO2 concentration may mitigate the adverse effects of drought through alteration of hormone production. The objective of this study was to determine whether elevated CO2 –enhanced drought tolerance in creeping bentgrass ( Agrostis stolonifera L.) was associated with the stimulation of tiller and stolon growth and the alteration of stress‐regulating and growth‐regulating hormone accumulation. Creeping bentgrass (cv. Penncross) plants were established for 24 d at ambient (400 μL L −1 ) or elevated (800 μL L −1 ) CO2 concentration and subsequently exposed to drought stress for 23 d by withholding irrigation. Drought stress caused significant reduction in leaf relative water content and tiller density, whereas both parameters, as well as stolon length, were maintained at significantly higher values in CO‐treated plants compared with those at ambient CO2 under drought stress. The positive effects of elevated CO2 on the maintenance of leaf hydration and the promotion of tiller density and stolon growth in creeping bentgrass exposed to drought stress could be associated with the suppression of drought‐induced accumulation of abscisic acid and the increase in the endogenous content of isopentenyladenosine, jasmonic acid, and the jasmonic acid precursor 12‐oxo‐phytodienoic acid. These results suggest that the elevated CO2 –enhanced growth of tillers and stolons in creeping bentgrass under drought stress could be regulated in part by the adjustment of endogenous hormone levels.